Histology of the primary tumor correlates with false positivity of integrated 18F-FDG-PET/CT lymph node staging in resectable lung cancer patients - Damirov, Fuad; Stoleriu, Mircea Gabriel; Manapov, Farkhad; Büsing, Karen-Anett; Michels-Zetsche, Julia D.; Preissler, Gerhard; Hatz, Rudolf A.; Hohenberger, Peter; Rößner, Eric (Diagnostics, 2023)
This study aimed to evaluate the diagnostic accuracy and false positivity rate of lymph node (LN) staging assessed by integrated 18F-fluorodeoxyglucose positron emission computed tomography (18F-FDG-PET/CT) in patients with operable lung cancer to the tumor histology. In total, 129 consecutive patients with non-small-cell lung cancer (NSCLC) undergoing anatomical lung resections were included. Preoperative LN staging was evaluated in the relationship to the histology of the resected specimens (group 1: lung adenocarcinoma/LUAD; group 2: squamous cell carcinoma/SQCA). Statistical analysis was performed by the Mann-Whitney U-test, the chi2 test, and binary logistic regression analysis. To establish an easy-to-use algorithm for the identification of LN false positivity, a decision tree including clinically meaningful parameters was generated. In total, 77 (59.7%) and 52 (40.3%) patients were included in the LUAD and SQCA groups, respectively. SQCA histology, non-G1 tumors, and tumor SUVmax > 12.65 were identified as independent predictors of LN false positivity in the preoperative staging. The corresponding ORs and their 95% CIs were 3.35 [1.10-10.22], p = 0.0339; 4.60 [1.06-19.94], p = 0.0412; and 2.76 [1.01-7.55], and p = 0.0483. The preoperative identification of false-positive LNs is an important aspect of the treatment regimen for patients with operable lung cancer; thus, these preliminary findings should be further evaluated in larger patient cohorts.